Can Serum Uric Acid Lowering Therapy Contribute to the Prevention or Treatment of Nonalcoholic Fatty Liver Disease? - Paschos, Paschalis; Athyros, Vasilios G.; Tsimperidis, Achilleas; Katsoula, Anastasia; Grammatikos, Nikolaos; Giouleme, Olga (Current Vascular Pharmacology, 2018)
Nonalcoholic fatty liver disease (NAFLD), the most common chronic liver disease in Western countries with potential progression to nonalcoholic steatohepatitis (NASH) and cirrhosis, is associated with cardiovascular disease (CVD) mortality. Several studies have reported a relationship between uric acid and NAFLD/NASH and it seems that serum uric acid (SUA) is a significant independent factor for the development of NAFLD. Potential mediating mechanisms include insulin resistance, endothelial dysfunction, and activation of inflammasome, especially NLRP3. Moreover, emerging evidence indicates a strong association between elevated SUA, metabolic syndrome (MetS), NAFLD, and CVD. The emphasis of the present review is whether common therapy of elevated SUA levels and NAFLD can improve compliance. There are several drugs with “off target” properties that show some separate benefit on SUA reduction (e.g. losartan) or NAFLD/NASH (pioglitazone); however, there is no randomized controlled trial (RCT) of a single drug with beneficial outcome for both diseases. Allopurinol reduces SUA levels and ameliorates NAFLD/NASH; however, no RCTs have been performed up to now to explore potential survival benefits. Atorvastatin, which has proven safe in NAFLD/NASH, reduces SUA levels, ameliorates NAFLD/NASH, prevents liver fibrosis, and above all substantially reduces CVD morbidity and mortality in comparison with those on statins but without NAFLD/NASH. This drug could be a solution to improve compliance in both diseases, which are prevalent and becoming even more common with the obesity, MetS, and type 2 diabetes mellitus epidemic.
Keywords: nonalcoholic fatty liver disease